4.0k views
5 votes
Solve each equation. Record your work and check your solution B. -6x-7=-1(-9+2x)

User Burkay
by
6.1k points

1 Answer

4 votes

Answer:

x = -4

Explanation:

So we start with the equation -6x - 7 = -1(-9 + 2x)

Then we distribute the -1 to the -9 and the 2x so we get: -6x - 7 = 9 - 2x

Now we make the x-values on one side and the numbers on the other side like this:

-6x + 6x - 7 - 9 = 9 - 2x + 6x - 9

-16 = 4x

Now we divide 4 / -16 which gives us x = -4

-16/4 = 4x/4

x = -4

Your welcome

User Aquaraga
by
5.6k points